What is the effect of interrupting prolonged sitting with frequent bouts of physical activity or standing on first or recurrent stroke risk factors? A scoping review. - Paul Mackie; Ishanka Weerasekara; Gary Crowfoot; Heidi Janssen; Elizabeth Holliday; David Dunstan; Coralie English (PLoS ONE)
The objective of this review was to ascertain the scope of the available literature on the effects of interrupting prolonged sitting time with frequent bouts of physical activity or standing on stroke and recurrent stroke risk factors. Databases Medline, Embase, AMED, CINAHL and Cochrane library were comprehensively searched from inception until 21st February 2018. Experimental trials which interrupted sitting time with frequent bouts of physical activity or standing in adults (≥ 18 years) were included. Comparison to a bout of prolonged sitting and a measure of at least one first or recurrent stroke risk factor was required to be included. Overall, 30 trials (35 articles) were identified to meet the inclusion criteria. Fifteen trials were completed in participants at an increased risk of having a first stroke and one trial in participants at risk of a recurrent stroke. Outcomes of hypertension and dysglycemia were found to be more favourable following predominately light- to moderate-intensity bouts of physical activity or standing compared to sitting in the majority of trials in participants at risk of having a first stroke. In the one trial of stroke survivors, only outcomes of hypertension were significantly improved. These findings are of significant importance taking into consideration hypertension is the leading risk factor for first and recurrent stroke. However, trials primarily focused on measuring outcomes of dysglycemia and without assessing a dose-response effect. Additional research is required on the dose-response effect of interrupting sitting with frequent bouts of physical activity or standing on first and recurrent stroke risk factors, in those high risk population groups.